2007
DOI: 10.1111/j.1745-7262.2007.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation in semen quality of swamp buffalo bulls (Bubalus bubalis) in Thailand

Abstract: Seasonal changes did not appear to cause deleterious changes in sperm quality in swamp buffalo AI-sires in tropical Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
5
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 9 publications
(10 reference statements)
9
36
5
1
Order By: Relevance
“…Our finding that sperm concentration and viability were lowest in samples obtained during summer is in agreement with those of previous reports in the human [37] and pig [38]. However, our finding is in contrast to those observed in water and swamp buffalo [39,40] of which optimal seminal quality was observed in samples obtained during rainy season and summer. The species differences between elephants and buffaloes may be due to variations in study location and techniques used for semen analysis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our finding that sperm concentration and viability were lowest in samples obtained during summer is in agreement with those of previous reports in the human [37] and pig [38]. However, our finding is in contrast to those observed in water and swamp buffalo [39,40] of which optimal seminal quality was observed in samples obtained during rainy season and summer. The species differences between elephants and buffaloes may be due to variations in study location and techniques used for semen analysis.…”
Section: Discussionsupporting
confidence: 91%
“…We speculate that the rise in ambient temperature in summer may affect sperm production [37] and sperm viability as has been reported in mice [43] and wild boars [44]. However, temperature may not influence sperm morphology, since a study on semen quality of swamp buffalo bulls used for artificial insemination under tropical conditions in Thailand showed that the proportion of morphologically normal spermatozoa were highest in summer [40] and a similar finding was observed in Asian elephant bulls in the present study. A complicating factor is that testes in elephants are intra-abdominal unlike the situation in other mammalian species where the testes are located in the scrotum to avoid damage to sperm from high body temperatures.…”
Section: Discussionmentioning
confidence: 91%
“…Similar report was not available in cattle and other species to compare the present study results. However, the motility and velocity parameters were measured by CASA in domestic animal species such as crossbred cattle (Perumal, 2008;Perumal et al, 2011), Bali cattle (Sarsaifi et al, 2013), buffalo (Anil Kumar et al, 2011;Koonjaenak et al, 2007), sheep (Kumar et al, 2010), goat (Kozdrowski et al, 2007), boar (Broekhuijse et al, 2012) and dog (Domosławska et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In experiment [9], in Thailand (tropical climate), semen collections were performed between winter and spring, when temperatures were mild. For buffaloes, this period was considered more suitable for the collection of semen, destined for freezing, since the ejaculates collected during these months of the year presented higher membrane integrity and stability, as well as better values for the movement (speed) patterns provided by CASA (computerassisted sperm analysis) to the samples which were thawed, and no effect was observed on the quality of the ejaculates.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, males subjected to thermal stress have their sexual activity depressed, with less testosterone production, due to the production of stressors secreted by metabolism [1,6,7,8,9,10]. In general, stress can be defined as any factor or change from the environment which interferes with homeostasis, which is a complex and dynamic system of equilibrium that governs the correct functioning of living organisms.…”
Section: Introductionmentioning
confidence: 99%